2018
DOI: 10.13057/biodiv/d200128
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial gastropod diversity, distribution and abundance in areas with and without anthropogenic disturbances, Northeast Algeria

Abstract: Belhiouani H, El-Hadef El-Okki M, Afri-Mehennaoui FZ, Sahli L. 2019. Terrestrial gastropod diversity, distribution and abundance in areas with and without anthropogenic disturbances. Biodiversitas 20: 243-249. The objective of this study was to establish an inventory of terrestrial gastropods from different sites in the northeast of Algeria. Several points were sampled from five various areas relatively affected by human activity. Areas prospected were an industrial area (El-Hadjar, Annaba), a mining area (Dje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…Several studies on land snail inventories have been carried out in several biotopes of Algeria, notably in the north-western (Damerdji, 2008(Damerdji, , 2013 and north-eastern regions (Larbaa & Soltani, 2013;Douafer & Soltani, 2014). Recently, a survey of gastropods was conducted in five areas of north-eastern Algeria (Belhiouani et al, 2019). However, we are not aware of a study on the biodiversity and abundance of terrestrial gastropods in other areas of northeast Algeria.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on land snail inventories have been carried out in several biotopes of Algeria, notably in the north-western (Damerdji, 2008(Damerdji, , 2013 and north-eastern regions (Larbaa & Soltani, 2013;Douafer & Soltani, 2014). Recently, a survey of gastropods was conducted in five areas of north-eastern Algeria (Belhiouani et al, 2019). However, we are not aware of a study on the biodiversity and abundance of terrestrial gastropods in other areas of northeast Algeria.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in the forest habitat have an adverse effect on the distribution and abundance of land snails being highly sensitive to climatic and other environmental changes (Bloch 2012). Belhiouani et al (2018) showed that areas with less to no anthropogenic disturbances in Northeast Algeria recorded high land snail abundance and diversity with ten species than to areas with anthropogenic disturbances that obtained only four species. Bloch (2012) suggested that regular cyclic disturbances such as typhoons or extreme dry season can cause a decline in land snail abundance but can recover over five or ten years.…”
Section: Discussionmentioning
confidence: 96%
“…Keanekaragaman jenis keong darat dapat dilihat kelimpahan jenis paling banyak ditemui pada malam hari, di lokasi hutan primer dan sekunder. Faktor yang mempengaruhi keanekaragaman adalah habitat, suhu dan kelembaban (Belhiouani, El-Okki, M.E., Afri-Mehennaoui, & Sahli, 2019). Tumpukan daun di atas serasah dapat membentuk lapisan penahan suhu malam dengan siang di luar serasah tidak mempengaruhi suhu di dalam serasah (Villeneuve, Thornhill, & Eales, 2019).…”
Section: Keanekaragaman Jenis Keong Daratunclassified